STRATEGI PENINGKATAN KEIKUTSERTAAN MAHASISWA FAKULTAS TEKNIK UNIVERSITAS BANGKA BELITUNG PADA BIDANG KOMPETISI - Wahri Sunanda (Simposium Nasional Mulitidisiplin (SinaMu), 2021)
Improving student achievement in the field of competition is one of the goals that need to be achieved in the strategic plan of the Faculty of Engineering, Universitas Bangka Belitung. Various analyzes based on strengths, weaknesses, opportunities and challenges have been compiled in an effort to produce the right strategy so that student achievement in the field of competition increases every year. With funding support from institutions and the collaboration of the academic community of the Faculty of Engineering, University of Bangka Belitung for the period 2018 - 2020, the increase in student achievement at the Faculty of Engineering, Universitas  Bangka Belitung at the local, regional, national and international levels is significant. This certainly has an impact on improving the quality of Tri Dharma and the graduates produced, as well as on the ranking of universities nationally